IMPROVING STUDENTS’ DESCRIPTIVE WRITING ACHIEVEMENT BY USING AUDIO-VISUAL OF THE SEVENTH GRADE OF MTsN PARE ACADEMIC YEAR 2016/2017 - ., kailani (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
Audio-visual media gives positive effect to the students. Students’ activity and students’ achievement in writing is improved by using Audio-visual media.  This study aimed to find out whether Audio-visual Media can improve students’ writing achievement of descriptive text at the seventh grade students of MTsN Pare in academic Year 2016/2017 or not. The design used is Classroom Action Research (CAR). The data collection method were test and observation. The subject of this research was the seventh grade students in class VII-I with the total of students is 40. The result shows that the students average in the first cycle is 77.27 and 52.5% students pass the success indicator while for the second cycle is 86.18 and 85.00% students pass the success indicator. Based on the means of the first cycle and second cycle, it shows that there is significant improvement from 77.27 to 86.18 and 52,5% to 85.00% students pass the indicator of success. Besides, students’ activities are more active and motivated in teaching learning process. Therefore, it is recomended that using Audio-visual Media can improve students’ writing achievement especially in descriptive text.